A new lease of life the Rumah Penghulu restoration 1995-1997 - Harun Rahman (Kuala Lumpur : Novista Sdn. Bhd, 1997)
Rumah Penghulu, the tradisional house that reflects a rich architectural styles enhanced by elements og Malay culture and tradition. Now Rumah Penghulu which in Bandar Baharu, Kedah is a heritage building safe by Badan Warisan Malaysia
Produced by Novista Sdn Bhd for Badan Warisan Malaysia
Editor, Harun Rahman, M. Baskaran ; script, Lara Ariffin, Chin Kek Mien
Narrator: Noraini Jane
Keywords: Architectural, Domestic -- Kedah; Malays -- Kedah; Housing -- Kedah